ANALISIS COGNITIVE LOAD THEORY DALAM PEMANFAATAN PAPAN INTERAKTIF DIGITAL (PID) PADA PEMBELAJARAN SEJARAH DI SMA: Penelitian Tugas Mata Kuliah - Muhammad Wildan Asrib; Farida Febriati (STKIP Subang, 2026)
The utilization of Digital Interactive Boards (PID) or Interactive Flat Panels (IFP) in classrooms promises a massive transformation of visual learning; however, its psychological and cognitive effectiveness is rarely evaluated . This research employs a descriptive qualitative approach with a single-case study design, aiming to analyze the tripartite interaction between teachers, students, and PID media using an analytical framework of Cognitive Load Theory (CLT). Employing a qualitative approach and case study method, participatory observations and semi-structured interviews were conducted during an Advanced History class in grade XI B1 at SMAN 16 Makassar. The field clinical findings indicate that the use of PID successfully maximizes germane load (meaningful processing) significantly when students are motorically and kinesthetically engaged through touch-screen features and interactive gamification apps. Students' metacognitive awareness revealed that direct interaction facilitates memory retention of complex historical material. Conversely, the teacher's instructional design, which avoids redundancy effects, successfully reduced extraneous load. However, extraneous load still spiked due to unexpected technical distractions (laptop notifications) and cognitive fatigue after the first 30 minutes caused by the intrinsic load of the material. This study concludes that no matter how advanced the technology, it will not be effective without precise techno-pedagogical design. Proposed recommendations include enabling a zero-distraction environment and cognitive duration segmentation.